TiO2(Fe3+) nanostructured thin films with antibacterial properties - Trapalis, Christos C.; Keivanidis, Panagiotis E.; Kordas, George C.; Zaharescu, Maria; Crisan, Maria; Szatvanyi, Alexandra; Gartner, M. (My University, 2003)
TiO2-based nanostructured Fe3+-doped coatings have been prepared by the sol-gel method on glass substrates. The coatings were characterized by X-ray diffraction and spectroellipsometry methods. The influence of Fe3+ dopant concentration, number of coatings, and calcination temperature on the films structure was established. The antibacterial activity against E. coli, has been studied applying the so-called antibacterial-drop test. The bactericidal activity for the above bacteria cells was estimated by relative number of bacteria survived calculated from the number of viable cells which form colonies on the nutrient agar plates. The coatings exhibited a high antibacterial activity, which was enhanced with the increase of the temperature of thermal treatment and formation of anatase crystalline structure. The long thermal treatment results in rutile crystalline structure formation followed by the decrease in the antibacterial activity of the coating. © 2003 Elsevier Science B.V. All rights reserved.
Keywords: TiO2 coatings; Fe3+/TiO2 coatings; Nanostructured films; Antibacterial coatings; Sol–gel method